Management of Educators and Education Personnel in the National Education System - Abdul Rasyid Baharuddin; Afriza Afriza; Hikmatul Hidayah (Education Achievement: Journal of Science and Research, 2023)
This research discusses the Management of Educators and Education Personnel in the National Education System, the importance of managing education and education personnel because one of the dominant factors that influences the quality of Indonesian National Education is the Role and Quality of Educators and Education Personnel. Therefore, this research was designed to provide an overview of the processes carried out in managing teaching and education personnel in accordance with the National Education System. The research method used in this research is library research, namely a series of activities relating to library data collection methods to obtain information data by collecting information related to the meaning, scope and process of educational policy. The data sources in this research are primary data sources and secondary data sources such as books, articles, etc. The results of the research in this article state that the management of teaching and education staff aims to utilize teaching and education staff effectively and efficiently to achieve optimal results while remaining in pleasant conditions. The components of educators and management of educational personnel are: starting with (1) employee planning, (2) human resources, (3) employee training and development, (4) promotion and transfer, (5) employee dismissal, (6) compensation and ( 7) provide assessments to employees or teaching and educational staff.